Pre-Natal Monitoring in the Primary Attention of the Brazilian Unified Health System - Moimaz, Suzely Adas Saliba [UNESP]; Garcia, Lea Lofego [UNESP]; Saliba, Nemre Adas [UNESP]; Saliba, Tânia Adas [UNESP] (Assoc Apoio Pesquisa & Saude Bucal-apesb, 2019)
Objective: To analyze prenatal care in the primary care of the Brazilian Unified Health System. Material and Methods: This is a survey cross sectional research with inquiry-type quantitative-qualitative approach. Data collection was performed in 28 cities of the Sao Paulo state, through on-site observations and interviews with health secretaries, coordinators of primary and oral health care. The following variables were analyzed: Primary health care services for pregnant woman as educational activities, presence of care and referral protocol and the organization of oral health care. Content analysis was performed for the answers of the open questions and the quantitative treatment of the discursive data was obtained through the categorial analysis. For the answers of the closed questions a descriptive analysis was performed. Results: The total number of participants interviewed was 84 managers. It was observed that 78.6 %% of cities carried out educational activities; 42.9% do not have an active care protocol and 57.1% do not have formal referral guidelines to high-risk pregnancies. The rapid tests for HIV, Syphilis, Hepatitis B and C were confirmed by 53.6% of managers and only 39.3% reported evaluating the vaccine situation. As to dental care, 71.4% of the municipalities do not have an established guideline; 46.4% reported that access occurs through spontaneous demand; 32.1% do not consider pregnant woman a priority care group and 67.9% have instituted prenatal dental care. Conclusion: Prenatal care has guaranteed educational activities, but it has deficiencies related to the work process and to the management of services, due, for the most part, to the inexistence of assistance and organizational protocols.
Keywords: Delivery of Health Care; Primary Health Care; Patient Care; Prenatal Care